Preliminary Study the Effect of Galbanic Acid on the Efficacy of Radiation Therapy on O26 Tumor Cells Implanted In Balb-C Mice - Morteza Rezaei kahkha; Shokouhozaman Soleymanifard; mehrdad iranshahi; samaneh soudmand salarabadi; elham tavakkoli; amir fotovati; Najme rezaei dovom (Iranian Journal of Medical Physics)
Introduction: In the present study we used Galbanic acid (GA) combined with radiation therapy to raise radiation efficacy. GA extracted from Ferula species and have anti-cancer properties. The purpose of this study is to investigate the effect of Galbanic acid on C26 tumor radiation sensitivity and The main challenge of this study is to deliver the drug to the tumor cells due to the hydrophobicity of Galbanic acid.Material and Methods: 28 inbred male Balb/C mice were injected subcutaneously with 500,000 C26 cells into the right flank. The mice were divided into 4 groups including group control, radiation alone (R), GA alone (GA), and both radiation and GA (R+GA). Life span, tumor growth and weight of the mice were evaluated. All analyzes were performed by the 26th version of SPSS and P value of less than 0.05.Results: The median lifespan in group R+GA was 28 days, which was longer than 20 days in group R, 22 days in group GA, and 16 days in the control group. The lifespan of the GA+R group was significantly higher than the other groups (P<0.05). The percentage of growth delay in group R+GA was 78%, while in group R and in group GA it was only 42% and 47%, respectively.Conclusion: The results showed that the lifespan and tumor growth rate of the mice that received combined treatment was longer and lower, compared to the two groups that received GA or radiation alone.